Simplified five-level voltage source inverter with level-phase-shifted carriers based modulation technique - Suroso Suroso; Daru Tri Nugroho; Abdullah Nur Azis; Toshihiko Noguchi (Institute of Advanced Engineering and Science, 2019)
A simplified circuit topology of the five-level pulse width modulation (PWM) inverter for DC-AC power conversion with no-isolated DC voltage sources and reduced switching device number is presented in this paper. The inverter circuit is based on the three-level H-bridge inverter configuration. The developed five-level inverter needs only five controlled power switches and four isolated gate drive circuits. Furthermore, the proposed topology does not require bidirectional power semiconductor controlled switches, hence a conventional discrete power MOSFETs or IGBTs can be used to build the inverter circuits. To obtain a better quality output voltage waveform, the level-phase-shifted carriers based sinusoidal pulse width modulation control was applied to produce a five-level PWM voltage waveform. The proposed inverter circuit was examined by using computer simulation with Power PSIM software. The basic principle operation of the inverter circuit was verified experimentally in laboratory using two non-isolated DC voltage sources as the inputs of the inverter’s prototype circuit. Some analysis of inverter’s output waveforms are provided and discussed.